Aplicación de la Metodología Design Thinking para el Diseño y Comercialización de Agendas Personalizadas en la Ciudad de Santa Marta (2023)
The present degree work is carried out showing different alternatives of personalized agendas, from the application of Design Thinking, since in the city there are few places that involve the user in the design of their agenda. The objective of this degree work is to apply the Design Thinking methodology for the design and marketing of personalized agendas in the city of Santa Marta. To achieve this, the methodology used in this research is mixed, considering qualitative and quantitative data; taking into account the descriptive, exploratory and documentary approaches. For its development, a collection of information was carried out using tools provided by the methodology in its different phases, which allowed said information to be analyzed and processed in order to later propose intelligent solutions to the needs and requirements of the users.